2019
DOI: 10.1021/acs.chemmater.9b01690
|View full text |Cite
|
Sign up to set email alerts
|

Ptychography of Organic Thin Films at Soft X-ray Energies

Abstract: The path to realizing low-cost, stable, and earth-abundant photoelectrodes can be enabled through a detailed understanding of the optoelectronic properties of these materials by combining theory and experimental techniques. Of the limited set of oxide photocathode materials currently available, CuFeO 2 has emerged as a promising candidate warranting detailed attention. In this work, highly compact thin films of rhombohedral (3R) CuFeO 2 were prepared via reactive cosputtering. Despite its 1.43 eV indirect band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…In an initial study, ptychography was performed on polymer blends that demonstrated 30-50 nm resolution with no discernable beam damage. 50 Although this is similar to the best achievable STXM resolution for similar samples, such an initial demonstration bodes well for eventual <10 nm chemically resolved images.…”
Section: Emerging Opportunities and Outlook For Rsoxssupporting
confidence: 59%
See 3 more Smart Citations
“…In an initial study, ptychography was performed on polymer blends that demonstrated 30-50 nm resolution with no discernable beam damage. 50 Although this is similar to the best achievable STXM resolution for similar samples, such an initial demonstration bodes well for eventual <10 nm chemically resolved images.…”
Section: Emerging Opportunities and Outlook For Rsoxssupporting
confidence: 59%
“…These techniques solve directly for the missing phase of the scattered wave to invert the scattering pattern from its Fourier transformed state back into an image of the sample itself. In an initial study, ptychography was performed on polymer blends that demonstrated 30–50 nm resolution with no discernable beam damage 50 . Although this is similar to the best achievable STXM resolution for similar samples, such an initial demonstration bodes well for eventual <10 nm chemically resolved images.…”
Section: Emerging Opportunities and Outlook For Rsoxsmentioning
confidence: 90%
See 2 more Smart Citations
“…Present understanding of the aggregated structure greatly benefits from the advances in characterization tools of soft matters. [45,47,416] For instance, R-SoXS has been a very powerful tool to analyze the structural parameters (domain size, [417,418] domain purity, [419] type and degree of orientation [420,421] ) of polymers blends in solid films. Use of other techniques (e.g., in situ neutron scattering [422] and cryo-TEM [423] ) will help to understand how the aggregated structure forms in solution state.…”
Section: New Characterization Tools For the Aggregated Structure Of Conjugated Polymersmentioning
confidence: 99%